Health and animal agriculture in developing countries - Zilberman, David; Otte, Joachim; Roland-Holst, David; Pfeiffer, Dirk (Natural Resource Management and Policy, 2012)
This book provides an overview of the state of animal agriculture and present methodologies and proposals to develop policies that result in sustainable and profitable animal production that will protect human and environmental health, enhance livelihood of smallholders and meet consumer needs. The book combines lessons of the past, factual foundation to understand the present, analytical tools to design and improve policies, case studies that provide both empirical grounding and applications of some of the strategies suggested in this book, and finally, a proposal for the way forward. The book is divided into five parts. The first section of the book will provide an analysis of the evolution of animal agriculture in the context of the development of farming systems over the years. The second part of the book will provide an overview of some of the major strands of literature on the economics and health of animal agriculture. The third and fourth sections of the book emphasize an important case study, avian influenza with applications in Southeast Asia and Africa. Finally, the book summarizes the state of knowledge and current trajectory of animal agriculture and provides policy recommendations to both control animal disease and support research that would lead to prosperous, sustainable animal agriculture in the future. This volume contains contributions from leading researchers in agricultural economics environmental economics, veterinary science, and natural resource management and will be of interest to academics and students in those fields as well as policy-makers in government or international organizations that focus on animal agriculture, health and the environment.